Выходцы из Волыни – жертвы политических репрессий в Крыму - Шевцова, Наталья; Shevtsova, N. (Волинський національний університет імені Лесі Українки, 2012)
На основе архивных источников рассматривается судьба выходцев из Волыни, которые в 20–40-х гг. ХХ в. были репрессированы на территории Крыма. On the basis of archival sources reflected in the fate of the Ukrainians of Volhynia, who at 20–40 years of the ХХ century were repressed in the Crimea.
People from Volhynia Victims of Political Repression in the Crimea
Keywords: политические репрессии; террор; арест; приговор; political repression; terror; arrest; punishment